Caprine farms in northwest region of Dominican Republic: Typologies according to livestock management and economic variables. - Angón, Elena; Perea, José Manuel; Valerio, Daniel; García, Antón; Acero, Raquel; Toro Mújica, Paula (Revista Científica de la Facultad de Ciencias Veterinarias, 2013)
The aim of this work was to identify and characterize the typologies of caprine systems in the Dominican Republic, which would determine their technical and economic performance. Data from 33 goat farms were collected by random sampling, where 51 technical and socio-economic variables were analyzed by multivariate analysis. This analysis allowed the selection of four principal components related to intensification, productivity, diversification, technological level and farm size. The subsequent cluster analysis classified the farms into three groups. Group 1, called Traditional subsistence, includes medium sized extensive farms with traditional management and low levels of productivity, technology and stocking rate. Group2 develops a semi-extensive system with increased levels of technology and use of external feed, higher ovine production and larger proportion of land in ownership even though it achieves low productive and economic performance. Finally, Group 3, called Traditional commercial, comprises large size farms with low levels of technology, applying external labour more efficiently and achieves acceptable economic results. Taking into account the characteristics of the systems identified, enhancing strategies to the caprine sector should be primarily aimed at group 1 and 2 farms, focusing on the improvement of low productivity and profitability levels.